An exploration of facilitators and barriers to patient navigator core functions with breast cancer patients: Implications for the development of a human-centered mHealth app - Alaina L. Carr; Naomi Vinod; Patrick Farha; Tan Lu; Maen J. Farha; Kristi D. Graves (Elsevier, 2023)
Objectives: To understand the barriers to core functions and workflow among patient navigators (PN) who navigate people diagnosed with breast cancer (BC). To identify how a mobile health (mHealth) app could assist PNs in providing care to BC patients. Methods: This qualitative research study used purposive sampling to recruit stakeholders (N = 33) from January to August 2021. We conducted individual semi-structured interviews with PNs (n = 11), oncology care providers (n = 12), and BC patients (n = 10). We used conventional content analysis to analyze the interview data. Results: Participants identified the following sociotechnical systems barriers in PN workflows that negatively impact BC patient care: 1) resources, 2) insurance coverage, 3) communication challenges, and 4) impact of logistical tasks. Participants identified the user experience, app features, and interoperability customizations to enhance PNs' provision of patient care as important design elements to include in a mHealth app. Conclusion: Feedback from stakeholders provided valuable insights into key design considerations, functions, and content areas for developing a mHealth app for PN use in BC care delivery. Innovation: This is one of the first studies to incorporate the human-centered design and sociotechnical systems frameworks to understand barriers to PN workflow and provision of BC patient care across the cancer care continuum.